Straightforward Synthesis and Characterization of Analcime@Nickel Orthosilicate Novel Nanocomposite for Efficient Removal of Rhodamine B Dye from Aqueous Media - Ehab A. Abdelrahman; Fawaz A. Saad; Mortaga M. Abou-Krisha; Abdalla M. Khedr; Zahrah Alqahtani (Inorganics)
Rhodamine B dye is a hazardous pollutant that poses significant risks to human health and aquatic ecosystems due to its toxic, carcinogenic nature and high chemical stability. To address this issue, analcime@nickel orthosilicate nanocomposites were synthesized via the hydrothermal method for efficient rhodamine B dye removal. Two nanocomposites were synthesized: EW (without a template) and ET (with polyethylene glycol 400 as a template, followed by calcination at 600 °C for 5 h). X-ray diffraction (XRD) confirmed the formation of analcime (NaAlSi2O6) and nickel orthosilicate (Ni2SiO4), with crystallite sizes of 72.93 nm (EW) and 63.60 nm (ET). Energy-dispersive X-ray spectroscopy (EDX) showed distinct distributions of oxygen, sodium, aluminum, silicon, and nickel. Field-emission scanning electron microscopy (FE-SEM) revealed irregular morphology for EW and uniform spherical nanoparticles for ET. The maximum adsorption capacities (Qmax) were 174.83 mg/g for EW and 210.53 mg/g for ET. Adsorption followed the pseudo-second-order kinetic model and was best described by the Langmuir isotherm, indicating monolayer chemisorption. Thermodynamic studies showed that adsorption was exothermic (ΔH = −45.62 to −50.92 kJ/mol) and spontaneous (ΔG < 0) and involved an entropy increase (ΔS = +0.1441 to +0.1569 kJ/mol·K). These findings demonstrate the superior adsorption efficiency of the ET composite and its potential application in dye-contaminated wastewater treatment.